Aging and thermocycling effects on adhesion of fiber posts to human radicular dentin - Layla Abu-Naba'a; M. Abu-Rujai (Universidade Estadual de Campinas, 2015)
Aim: This in vitro study evaluated the effect of different aging periods and thermocycling on the adhesion of fiber posts to human dentin at different depths. Methods: Twenty teeth were cleaned, decoronated, and endodontically treated. After one week, root filling was removed and a 10-mm post space was prepared. Posts (RelyX™ Fiber size 2) were cemented with a self-adhesive resin cement (RelyX™ Unicem) and light cured. Specimens (n=4, each) were stored in 100% humidity (0 day, 7 days, 1 month, 3 months) or thermo-cycled (at 7 days, 10,000 cycles, 5-55C°, 30 s). Four 1-mm-thick sections were obtained from each tooth and a push-out test was performed and results compared. Results: There was a significant difference (ANOVA p<0.05) between the means of push-out test results (MPa ± SE) at different storage periods: 24 hours: 15.2 ± 1.4; 7 days: 16.8 ± 1.5; 1 month: 20.3 ± 1.8; and 3 months: 12.5±2.0. Shear strength was significantly different (Chi-square, p<0.05) at the different slice positions. Apical sections had an increase in strength at 7 days and 1 month, but without statistical significance. The coronal section increased significantly between 0 and 7 days. All sections had reduced strengths between 1 and 3 months, but only the apical sections decreased significantly (ANOVA, p<0.05). There was no significant difference in shear strength between thermally cycled and non-cycled samples (MPa/SE 16.7± 5.9, MPa/SE 16.0 ± 9.3)(p>0.05). Conclusions: Long-term storage of test samples affected the bond strength of fiber posts to radicular dentin variably, and should be considered as part of invitro testing.